2021
DOI: 10.1080/14693062.2021.1977599
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating the speed and scale of climate finance in the post-pandemic context

Abstract: In this paper, we examine how to trigger a wave of low-carbon investments compatible with the wellbelow 2°C target of the Paris Agreement in the current post-pandemic context of increasing private and public debt. We argue that one major obstacle to catalyzing global excess savings at sufficient scale and speed on climate mitigation, and to 'greening' economic recovery packages, lies in the upfront risks of low-carbon investment. We then explain why public guarantees should be the preferred risk-sharing instru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 48 publications
1
22
0
Order By: Relevance
“…By taking into consideration the reduction of investments in fossil fuels, they further claimed an estimate of 20 billion US$/year until 2024 (thereafter, additional total energy investments ). They concluded that “in sum, a small fraction of announced COVID-19 economic recovery packages could provide the necessary financial basis for a decided shift toward a Paris Agreement-compatible future.” Although we agree with A20 and others that COVID-19 stimulus funds may offer an opportunity to boost climate actions (Hepburn et al 2020 ) and may be important for reducing upfront risks that can deter low-carbon investments (Hourcade et al 2021 ), we nevertheless believe that the conclusions by A20 misrepresent the grand challenges that climate change mitigation entails (IPCC 2018 ). In our view, their analysis and other similar claims need to be balanced by the following five arguments.…”
Section: Introductionsupporting
confidence: 65%
See 2 more Smart Citations
“…By taking into consideration the reduction of investments in fossil fuels, they further claimed an estimate of 20 billion US$/year until 2024 (thereafter, additional total energy investments ). They concluded that “in sum, a small fraction of announced COVID-19 economic recovery packages could provide the necessary financial basis for a decided shift toward a Paris Agreement-compatible future.” Although we agree with A20 and others that COVID-19 stimulus funds may offer an opportunity to boost climate actions (Hepburn et al 2020 ) and may be important for reducing upfront risks that can deter low-carbon investments (Hourcade et al 2021 ), we nevertheless believe that the conclusions by A20 misrepresent the grand challenges that climate change mitigation entails (IPCC 2018 ). In our view, their analysis and other similar claims need to be balanced by the following five arguments.…”
Section: Introductionsupporting
confidence: 65%
“…Energy investments into low-carbon energy and away from fossil fuels are most cost-effectively induced by carbon pricing complemented with subsidies for technology development and the expansion of low-carbon infrastructure (Sandén and Azar 2005 ; Baranzini et al 2017 ; Hourcade et al 2021 ), unlike what is implicitly assumed when comparing the face values of recovery public funds with energy investments in IAMs. It is well-established that carbon pricing should be the backbone to meet the Paris Agreement targets cost-effectively (Stiglitz et al 2017 ).…”
Section: Five Arguments For a More Comprehensive Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Public debt affects emissions in many ways [3,43]. First, variation in debt can change macroeconomic policy and GDP growth, thus greatly impacting energy use and subsequently, CO 2 emissions [17].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Now, policymakers are deciding on recovering the economy through debt financing [2]. The pandemic has increased expenditure demands as countries strive to lessen the side effects of the crisis, while revenues have decreased due to dull growth and trade, together pushing debt burdens to a higher level [3]. However, as in former crises, only the concentration on economic recovery will exert devastating impacts on the sustainable development goals (SDGs) [4].…”
Section: Introductionmentioning
confidence: 99%